Effectiveness of Extension Methods: A Case of Western Mid-Hills in Nepal - Baral, P.; Paudel, R.; Adhikari, B. B.; Sudedi, M.; Jaishi, M. (Journal of the Institute of Agriculture and Animal Science, 2018)
A study was carried out to assess the effectiveness of the extension methods used by IRRI-STRASA project in three municipalities namely Bhanu, Rainas and Sundarbazar of Lamjung and Tanahun districts. 101 sample households were taken purposively from beneficiaries of the project and survey design with structured questionnaire was used for data collection. The study showed that the participation of farmers in project was in increasing trend; mainly for technical support and assistance from the project. The group extension method was highly preferred by the farmers and it was found that the extension personnel contact under the project was satisfactory with methods like minikit, demonstrations and trainings having higher contact, thus helping in increasing social network of farmers. About 39 percent of study household had women participation at decision making level and 8 percent had socially mobilized level which was due to awareness and participation in the project activities. The adoption of the improved varieties was about 95 percent in the households, the reason for such high adoption being increased yield, lower cost of production, climate adaptability, higher pest resistance and higher grain quality. Finally, the overall effectiveness index of project was assessed using five indicators and was found 0.64 implying that the project was effective and the methods were classified into two groups: effective methods (trainings, study visits and tours, minikit, group and demonstrations) and moderately effective methods (PVS, FFS and ICTs).